2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00263.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heart rate on augmentation index and central arterial pressure in humans

Abstract: Arterial stiffness is an important determinant of cardiovascular risk. Augmentation index (AIx) is a measure of systemic arterial stiffness derived from the ascending aortic pressure waveform. The aim of the present study was to assess the effect of heart rate on AIx. We elected to use cardiac pacing rather than chronotropic drugs to minimize confounding effects on the systemic circulation and myocardial contractility. Twenty‐two subjects (13 male) with a mean age of 63 years and permanent cardiac pacemakers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
679
12
20

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(772 citation statements)
references
References 32 publications
45
679
12
20
Order By: Relevance
“…10,11 A number of nonpathological factors influence augmentation index and PWV. It has been consistently reported that age, 1,12 height, 13,14 heart rate 15,16 and gender 12,14 influence augmentation index, whereas PWV appears to be a more robust stiffness measure influenced by fewer factors including age 1,5 and heart rate. 17 However, despite the wide use of both augmentation index and PWV, there are controversial results in the literature regarding the relation between both stiffness measures and blood pressure, the classical haemodynamic parameter.…”
Section: Introductionmentioning
confidence: 97%
“…10,11 A number of nonpathological factors influence augmentation index and PWV. It has been consistently reported that age, 1,12 height, 13,14 heart rate 15,16 and gender 12,14 influence augmentation index, whereas PWV appears to be a more robust stiffness measure influenced by fewer factors including age 1,5 and heart rate. 17 However, despite the wide use of both augmentation index and PWV, there are controversial results in the literature regarding the relation between both stiffness measures and blood pressure, the classical haemodynamic parameter.…”
Section: Introductionmentioning
confidence: 97%
“…We noted a 7.1% reduction in AIx that is comparable to those reported by others after single bouts of exercise longer than 10 min. As the AIx is inversely related to HR and is influenced by Tr, 26,29 it can be argued that the post-exercise reduction in AIx may be partially mediated by changes in these factors. However, as opposed to previous studies that have shown reductions in the AIx along with increases in HR 30 min after exercise, 9-11 HR and Tr did not change in response to PV, and hence, they did not influence the AIx response.…”
Section: Discussionmentioning
confidence: 99%
“…AIx was normalized to a heart rate (HR) of 75 beats min À1 (AIx@75) as it is influenced by HR. 26 Transit time of the reflected wave (Tr) indicates the round-trip travel of the forward wave to the peripheral reflecting sites and back to the aorta. 25 AIx and Tr have been used as markers of wave reflection and aortic stiffness, respectively.…”
Section: Experimental and Vibration Protocolmentioning
confidence: 99%
“…The lower heart rate in CSX patients is unlikely to entirely account for the AIx increase because (1) ejection duration was similar between groups, (2) significant differences in AIx remained between groups after statistical correction for heart rate and (3) the heart rate difference between groups (8 b.p.m.) would only account for about 3% AIx, 11 whereas the actual difference was a statistically significant 7%. Moreover, MAP and height are well known to correlate with AIx, but these associations were only demonstrated in the controls and not the CSX patients.…”
mentioning
confidence: 84%